X+27-14=-15

Simple and best practice solution for X+27-14=-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+27-14=-15 equation:


Simplifying
X + 27 + -14 = -15

Reorder the terms:
27 + -14 + X = -15

Combine like terms: 27 + -14 = 13
13 + X = -15

Solving
13 + X = -15

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + X = -15 + -13

Combine like terms: 13 + -13 = 0
0 + X = -15 + -13
X = -15 + -13

Combine like terms: -15 + -13 = -28
X = -28

Simplifying
X = -28

See similar equations:

| 6x^2-1=2 | | 8x-(4+5x)=17 | | 7x-5(5x+8)=11+8(5-4x) | | c(m)=0.15+0.75 | | 8x-6=8x+20 | | (2x+11)=(10x-17) | | 144x^2+732x-36=0 | | 3(4r-7)-4(r-3)= | | 4-2(x-5)=1 | | 7c+3=4c+21 | | 16/128=24/x | | 13x+4y=7 | | 5p+4=19 | | 2(p+3)=3 | | 3(t-3)+5t=4(2t+4)-12 | | (10x-3)=(8x+1) | | 7x+4forx=6 | | 10x(4+2)= | | 9y^2+8y-12=6y | | Logx(8-2x)=2 | | 3p-13=11+9p | | 5z=9z-8 | | 3p-13=11+9 | | (5x-8)2=(5x+12)2 | | -6(x-2)=x+5 | | t*4-2=16 | | 4x^4+2x^2-20x=0 | | X+5*3x-2= | | (3-5x)/(2x-4)=0 | | 2x+3x=15findx | | 18x^2/10y^2*15y^3/24x | | 23-2=x-2+7 |

Equations solver categories